Strategy to Develop Project by Using Hybrid Approach (Agile and DevSecOps Methodologies) - Paul, Sunaina (Digital Repository of Theses - SSBM Geneva, 2025)
A project is undertaken to create unique product, result, or services by executing set of activities to meet project objective. The success of project is measured towards achievement of project objective, project quality, timelines, budget compliance and degree of customer satisfaction. Currently, in competitive business environment product development is more dynamic and changing very frequently. The common challenges observed with failed project which has experienced overrun & schedule delays as compared to successful project are related to project planning, estimation, Accepting/Managing changes in requirements and quality management. Today in era of frequently changing technology and requirement, an adaptive approach is much needed for the product development. At present for the most complex and highly unstable projects, the Agile methodologies are implemented to increase the efficiency of the project and to exceed the customers satisfaction. This research will provide an insight on the challenges that management and team face after transitioned to Agile Project Management. Outcome of this research would be useful for project managers who has transitioned to Agile Project Management but are unaware of the difficulties. It will also help department in the organization who recently transitioned to Agile Project Management and revolutionize the workflow from within. Finally, team will get useful insights on how to handle this change, if they do not have any previous agile project management experience. In addition, it will propose a new conceptual framework i.e., hybrid framework that comprises of Agile and DevSecOps methodologies to enhance the predictability and efficiency of project. Key words: Project, Traditional Project management, Customer satisfaction, Agile, DevSecOps, Predictability.